Novel Inhibitors for MDM2-MDM4 E3 Ligase Potently Induce p53-Indepedent Apoptosis in Drug-Resistant Leukemic Cells - Rati Lama; Joseph M. Fose; Diana Martín; Inés G. Muñoz; Eunice S. Wang; Pamela J. Sung; Sherry R. Chemler; Xinjiang Wang (Molecules)
MDM2 and MDM4 are major negative regulators of tumor suppressor p53. Beyond regulating p53, MDM2 possesses p53-independent activity in promoting cell cycle progression and tumorigenesis via its RING domain ubiquitin E3 ligase activity. MDM2 and MDM4 form heterodimer polyubiquitin E3 ligases via their RING domain interaction. Inhibitors disrupting p53 interaction with MDM2/MDM4 are in clinical trials in patients bearing wild-type p53 cancers. However, these inhibitors are not designed to work for p53-null/mutant cancer cells. Owing to the importance of the E3 ligase of MDM2 in its p53-independent oncogenic activity, inhibitors targeting the E3 ligase activity of MDM2-MDM4 are desirable for p53-mutant cancer cells. Here, we report the development of such inhibitors with pro-apoptotic activity in p53-null leukemic cells. Among analogues of MDM2-MDM4 E3 ligase inhibitors, we initially identified MMRi36 as a potent pro-apoptotic compound in p53-null leukemic cells with acquired drug resistance. MMRi36 acts as an activator of MDM2-MDM4 E3 ligase by stabilizing MDM2-MDM4 heterodimers and promotes MDM2/MDM4 degradation in cells. Interestingly, replacement of the sulfur in 1,3,4-thiadiazole MMRi36 with a carbon led to identification of pyrazole MMRi36C that dissociates the MDM2-MDM4 RING heterodimers, inhibits the E3 ligase activity of the complex, and induces p53 protein accumulation, but retains the p53-independent pro-apoptotic activity. A brief SAR study identified a fluorine derivative of MMRi36C with improved pro-apoptotic activity. This study discovered a novel class of compound that targets MDM2-MDM4 ubiquitin E3 ligase activity for apoptosis induction in p53-mutant cancer cells.